The Routledge Handbook of Transatlantic Security. - Hanhimki, Jussi (Taylor & Francis, 2010)
What lies behind the growing and continuing European dependency on security policy on the United States and what are the political consequences of this? Is this dependency likely to continue or will an independent European Common Foreign and Security Policy eventually emerge? This title addresses these questions.